Degradation Of Congo Red Based On Natural Coagulant (Moringa Oleifera) - Ramadani, Tarikh Azis; Ramadhani, Dhiya’ Arnada; Fatmawati, Meilinda Eka; Mayangsari, Novi Eka; Astuti, Ulvi Pri (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
The release of dyes into the environment can have deleterious effects. therefore, their handling must be done in a conscientious manner. One method that can be employed is coagulation-flocculation. The employment of natural coagulants has been demonstrated to mitigate the deleterious effects of polluting compounds on the ecosystem. Moringa oleifera, a plant native to tropical regions, including Indonesia, is a natural source of coagulants. Moringa oleifera plants are extracted using sodium chloride to isolate protein active ingredients. The utilization of a natural coagulant derived from moringa oleifera was implemented with the objective of ameliorating the deleterious effects of congo red. The effectiveness of the natural coagulant was evaluated based on the effect of initial concentration and coagulant dosage. The initial concentration and dose of coagulant exhibited a direct correlation with the efficiency of reducing congo red. An increase in the initial concentration resulted in a concomitant decrease in efficiency, while an increase in the coagulant dose demonstrated a corresponding increase in efficiency. The highest removal efficiency value was obtained when the coagulant dose was 100 ppm and the initial concentration was also 100 ppm. The consequence of this condition was a 99.46% reduction in efficiency of the congo red.